Quality of Life at Work of Janitors Workers - Rodríguez Nieto, Ma. Concepción; Himénez-Sanchez, Oswaldo; Peña-Moreno, José Armando; Ibarra-González, Víctor Hugo (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2018)
The aim of the study was to analyze the perception of quality of life in the work of janitor employees. The design was descriptive with a mixed approach. The 11 janitor workers of a Faculty of a public university participated and they responded individually to a questionnaire. In addition, eight of them participated in semi-structured interviews where the theme of study was addressed. The results showed that janitor workers have a high general perception of the quality of life at work associated with a high level of subjective wellbeing and satisfaction with work, good health and social interaction with coworkers, boss and members of the organization. For all janitor workers, the family is a great motivator and support in their daily lives and works. However, a work-family imbalance was found that women perceive greater than men.